FUNCTIONING AND FALLS IN THE INSTITUTIONALIZED ELDERLY: PROPOSALS FOR NURSING ACTIONS - Ariane Minussi Feliciani; Silvana Sidney Costa Santos; Rafaela Vivian Valcarenghi (Cogitare Enfermagem, 2011)
This is an evaluative piece of research which aimed to propose improving actions for a long-term elderly care center in Rio Grande do Sul, Brazil, which could help the nurses to maintain residents’ functioning and reduce their falls. A public-policy-based evaluative tool was built, tested and applied, for use by nurses. With this tool, first applied in September 2009, it was possible to identify and present actions which might contribute to maintaining residents’ functioning and reducing falls. It is hoped that this initiative, apart from aiding the nurse in care of the elderly, may promote the connection between the workplace and higher learning so that other areas with potential for strategic actions may be identified and optimized for nursing care of the elderly residents in long-term care facilities.